Fertility Desire, Knowledge of Prevention of MCT of HIV and Associated Factors Among Men and Women Attending ART Clinic at Public Health Institutions of West Shoa Zone, Oromia, Ethiopia, 2020 - Dina GD (Dove Medical Press, 2021)
Gurmesa Daba Dina, Bikila Tefera Debelo, Daniel Belema, Kababa Temesgen Danusa, Rebuma Muleta Midwifery Department, College of Medicine and Health Science, Ambo University, Ambo, EthiopiaCorrespondence: Bikila Tefera Debelo Email werkitef@gmail.comBackground: Globally, the human immunodeficiency virus (HIV) affects young people in their reproductive years. Most of the studies conducted in Ethiopia focus on the fertility desire of women of reproductive age and did not give due consideration to the men’s fertility perspective. Thus, this study aimed to assess the fertility desire, knowledge of prevention of mother to child of HIV (PMTCT), and associated factors among HIV-positive men and women attending ART clinic at west Shewa zone, Oromia region, Ethiopia, 2020.Methods: Facility-based cross-sectional study design was applied to identify fertility desire, PMTCT knowledge, and associated factors among 590 HIV-positive reproductive age group men and women attending ART clinics at public health institutions of West Shewa zone. Data were collected by pre-tested structured questionnaires and analyzed using SPSS version 22. Binary logistic regression analysis was used to examine the association of predictors on fertility desire and knowledge about PMTCT. Odds ratio, 95% CI, and P value 0.05 were used to measure the statistical association.Results: The prevalence of fertility desire and knowledge of PMTCT in the study area were 58.8% and 30.7%, respectively. The odds of fertility desire were higher among the respondents aged > 25 years [AOR=4.64, 95% CI (2.75– 7.85)], housewives [AOR=3.14, 95% CI (1.90– 5.21)], merchants [AOR=5.31, 95% CI (2.55– 11.05)], ART use for ≤ 5 years [AOR=5.13, 95% CI (2.37– 11.12)] and among those voluntarily tested to know their HIV status [AOR=2.16, 95% CI (1.30– 3.58)]. Besides, the odds of fertility desire were low among husband who cannot read and write [AOR=0.07, 95% CI (0.02– 0.23)], primary education [AOR=0.22, 95% CI (0.09– 0.56)], and secondary education [AOR= 0.32, 95% CI (0.14– 0.73)] when compared with husband education of college and above. Likewise, the odds of PMTCT knowledge were higher among the respondents aged less than 25 years [AOR=2.53, 95% CI (1.32– 4.86)] who undergone voluntary testing during HIV diagnosis reasons [AOR=1.55, 95% CI (1.03– 2.35)], and ART use for more than five years [AOR=1.94, 95% CI (1.26– 2.98)].Conclusion: Younger age, husband education, occupation, recent HIV test, and voluntary testing were significantly associated with fertility desire. Likewise, the younger age group, voluntary testing and counseling, and those on ART for more than five years had higher odds of PMTCT knowledge. Therefore, strengthening voluntary testing and counseling strong counseling on PMTCT throughout the follow-up care and involvement partners is of paramount importance should be insured to decrease MTCT.Keywords: PMTCT knowledge, fertility desire, west Shewa, Ethiopia